16×2-56x+49=0

Rewrite 16×2 as (4x)2.

(4x)2-56x+49=0

Rewrite 49 as 72.

(4x)2-56x+72=0

Check the middle term by multiplying 2ab and compare this result with the middle term in the original expression.

2ab=2⋅(4x)⋅-7

Simplify.

2ab=-56x

Factor using the perfect square trinomial rule a2-2ab+b2=(a-b)2, where a=4x and b=-7.

(4x-7)2=0

(4x-7)2=0

Set the 4x-7 equal to 0.

4x-7=0

Add 7 to both sides of the equation.

4x=7

Divide each term by 4 and simplify.

Divide each term in 4x=7 by 4.

4×4=74

Cancel the common factor of 4.

Cancel the common factor.

4×4=74

Divide x by 1.

x=74

x=74

x=74

x=74

Solve using the Square Root Property 16x^2-56x+49=0